Structural Determinants for the Differences in Voltage Gating of Chicken Cx56 and Cx45.6 Gap-Junctional Hemichannels - Tong, Jun-Jie (Biophysical Society, 2006)
The voltage- and calcium-dependent gating properties of two lens gap-junctional hemichannels were compared at the macroscopic and single channel level. In solutions containing zero added calcium and 1 mM Mg, chicken Cx56 hemichannels were mostly closed at negative potentials and application of depolarizing voltage clamp steps elicited a slowly activating outward current. In contrast, chicken Cx45.6 hemichannels were predominantly open at negative potentials and rapidly closed in response to application of large depolarizing potentials. Another difference was that macroscopic Cx45.6 currents were much smaller in size than the hemichannel currents induced by oocytes with similar amounts of cRNA for Cx56. The aim of this study was to identify which regions of the connexins were responsible for the differences in voltage-dependent gating and macroscopic current amplitude by constructing a series of chimeric Cx45.6-Cx56 channels. Our results show that two charged amino acids that are specific for the α3-group connexins (R9 in the N-terminus and E43 in the first extracellular loop) are important determinants for the difference in voltage-dependent gating between Cx45.6 and Cx56 hemichannels; the first transmembrane-spanning domain, M1, is an important determinant of macroscopic current magnitude; R9 and E43 are also determinants of single channel conductance and rectification.